The Influence of Distribution and Pricing on Purchase Decisions at the Sari Roti Outlet of PT Indosari Niaga Nusantara in Parepare - Sulawati Sulawati; A. Fitri Sugi Angka; Arfandy Dinsar (Invoice : Jurnal Ilmu Akuntansi, 2025)
This study aims to determine whether Distribution and Price have a partial and simultaneous effect on the Purchase Decision of Sari Roti outlets at PT INDOSARI Niaga Nusantara Parepare. In this study, the population sampled consisted of 45 people. The research method used is data description with the help of Statistical Product and Service Solutions (SPSS) software version 25.The data collection methods used include Interviews, Documentation, and Observation. This research involves several tests, including Validity Test, Reliability Test, Multiple Linear Regression Analysis, as well as t-test (partial), F-test (simultaneous), and Coefficient of Determination (R²). These results indicate that Distribution (X1) has a significant partial effect on the Purchase Decision of Sari Roti Outlet PT INDOSARI Niaga Nusantara Parepare. This is based on the t-count value of 2.677 > t-table value of 2.018 and a significance value smaller than 0.05 (0.000 ≤ 0.05). Price (X2) has a significant partial effect on the Purchase Decision of Sari Roti Outlet PT INDOSARI Niaga Nusantara Parepare. This is based on the t-count value of 5.648 > the t-table value of 2.018 and a significant value of 0.000 ≤ 0.05. Distribution and Price simultaneously affect the Purchase Decision of Sari Roti Outlet PT INDOSARI Niaga Nusantara Parepare. This is based on the calculated F value of 62.069 > the table F value of 2.83 with a significance value of 0.000 < 0.05.